Changing Teaching Practices : The Impact of a Professional Development Program on an English Language Teacher (2018)
ABSTRACT: Professional development programs in the form of learning communities offer teachers the possibility of improving their practice, and support them in meeting the demands that the government and society have assigned them, provided that such programs are well designed and developed. These programs may provide teachers with the necessary support and learning opportunities to face the new academic demands and be able to integrate these with the social and moral dimension of schooling. However, in Colombia the idea of schoolteachers working in learning communities as a means of professional development is scarce. Therefore, little systematic research has been conducted in the country to understand their impact on teachers’ learning, and even more specifically on their practice; only a few studies have been conducted to understand this issue. The case study reported here focused on understanding how an English teacher changed her teaching practice with the support of a facilitator in a teacher learning community. Data was gathered through interviews, class observations, recorded meetings, teachers’ planning units and pedagogical materials. Results indicate that the teacher experienced changes in her teaching practice related to new patterns of teaching behavior and methodology. However, there were some aspects of these two components that she changed only to a limited extent. As a result, she faced some difficulties with students and some contextual factors that affected her learning process. This study reveals several contributions that a learning community can offer to in-service teachers to improve their teaching practice and the complexity of teacher learning under certain circumstances.